Inteligencia emocional y el rendimiento académico de los estudiantes de la carrera de Psicología Clínica de la Universidad Nacional de Loja periodo 2022-2023 - Izquierdo Gallegos, Hipatia Pamela (2023)
The general objective of this research was to determine the relationship between emotional intelligence and academic performance of a group of university students. The study has a quantitative approach, with a non-experimental, cross-sectional, descriptivecorrelational design. A sample of 73 university students from the Clinical Psychology program of the Universidad Nacional de Loja was selected by simple random probability sampling. The instruments used were the Emotional Intelligence Test TMMS-24 and the students' grade records for the academic period April-September 2022. The data analysis was performed by means of the Stata/MP14.0 program. The findings obtained reveal that most of the study sample presents an adequate level of emotional intelligence in the dimensions of attention, clarity and emotional regulation; likewise, it is evident that the students participating in the study are at an excellent level of academic performance. Finally, a positive and negative relationship was found between the study variables, that is, the higher the emotional attention and emotional repair, the higher the academic performance, while the higher the emotional clarity, the lower the academic performance; however, these relationships are not statistically significant